2004
DOI: 10.1074/jbc.m407382200
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's Sarcoma-associated Herpesvirus-encoded Viral Interleukin-6 Is Secreted and Modified Differently Than Human Interleukin-6

Abstract: Viral interleukin-6 (vIL-6) is a homolog of cellular IL-6 that is encoded by the Kaposi's sarcoma-associated herpesvirus (KSHV) genome. vIL-6 binds to the IL-6 signal transducer gp130 without the cooperation of the IL-6 high affinity receptor to induce STAT3 DNA binding and cell proliferation. Although vIL-6 is believed to be important in the pathogenesis of KSHV-induced diseases, its secretion and post-translational modifications have not previously been characterized. Pulse-chase analysis revealed that the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 70 publications
2
66
0
Order By: Relevance
“…Using this cell model system, secretion of vIL-6 was completely eliminated. Recently, a model of an intracellular signaling mechanism of vIL-6 was reported (43), and this model is further supported by our data. It was shown that only a small proportion of synthesized vIL-6 is secreted and that intracellular signal activation via a vIL-6-gp130 interaction in the ER is predominant.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Using this cell model system, secretion of vIL-6 was completely eliminated. Recently, a model of an intracellular signaling mechanism of vIL-6 was reported (43), and this model is further supported by our data. It was shown that only a small proportion of synthesized vIL-6 is secreted and that intracellular signal activation via a vIL-6-gp130 interaction in the ER is predominant.…”
Section: Discussionsupporting
confidence: 77%
“…It was speculated that only a small proportion of synthesized vIL-6 is secreted and that intracellular signal activation via a vIL-6-gp130 interaction in the ER is predominant (43). To evaluate this model and to demonstrate the relevance of our scFv-vIL-6-ER retention strategy, we generated a vIL-6 cDNA C-terminally fused to the ER retention signal KDEL.…”
Section: Fig 3 Mapping Of the Vil-6 Epitopes Recognized By Mavmentioning
confidence: 99%
See 1 more Smart Citation
“…Human IL-6 forms hexameric signaling complexes comprised of two gp80 receptor subunits, two gp130 signal transducers, and two hIL-6 molecules (gp80 2 -gp130 2 -IL-6 2 ) (10). Viral IL-6 can also form signaling hexamers at the cell surface, but its unique signaling from the endoplasmic reticulum (ER) occurs via tetrameric complexes (gp130 2 -vIL-6 2 ) exclusively (8,12,15,16). Viral IL-6 can be expressed during latent stages, in addition to lytic stages, of the viral life cycle (8,17).…”
Section: H Uman Herpesvirus 8 (Hhv-8) Is Associated With Multicentricmentioning
confidence: 99%
“…The common hypothesis is based on the fact that KSHV encodes many viral lytic genes whose products are secreted factors homologous to cellular chemokines, cytokines, and growth factors, such as the viral interleukin (IL)-6 and the three viral chemokines (vCCL-1, -2, and -3, or alternatively named viral macrophage inflammatory protein, vMIP-I, -II, and III) (Nicholas, 2003). The vIL-6 is produced and released by infected cells during lytic infection and activates cell proliferation (Meads & Medveczky, 2004) and local angiogenesis (Aoki et al, 1999), while the viral MIPs are agonists for cellular chemokine receptors and exhibit angiogenic properties (Boshoff et al, 1997;Endres et al, 1999;C. Liu et al, 2001;Stine et al, 2000).…”
Section: Contribution Of Latency and Lytic Replication To Ks Tumorigementioning
confidence: 99%